GLUT 1 receptor expression and circulating levels of fasting glucose in high grade serous ovarian cancer. Issue 2 (14th July 2017) - Pizzuti, Laura; Sergi, Domenico; Mandoj, Chiara; Antoniani, Barbara; Sperati, Francesca; Chirico, Andrea; Di Lauro, Luigi; Valle, Mario; Garofalo, Alfredo; Vizza, Enrico; Corrado, Giacomo; Tomao, Federica; et al.
Abstract : In recent years, the poorly remarkable goals achieved in terms of patients' important outcomes for ovarian cancer have fueled our interest toward the study of its metabolic roots. Within this research pipeline, we assessed the association between the expression of the glucose transporter GLUT1, as expressed at the tumor tissue level, and circulating pre‐surgical levels of fasting glucose in a case series including data from 40 patients with high FIGO stage serous ovarian cancer. Patients who provided data to the current analysis were randomly selected from a larger cohort. To our purposes, the procedures related to serum and tissue collection, storage and biomarker assessment were highly standardized and centralized at the institutional laboratories. The GLUT1 antibody SPM498 SPRING (REF. E13810) was used at a 1:500 dilution in 2 µm slides. Staining for GLUT1 was observed at the cell membrane level in all the cases assessed, but strong staining was described in 29 (72.5%) of them. The agreement between the two independent reviewers was 100%. Strong GLUT1 staining was inversely associated with circulating levels of fasting glucose, with a particularly striking difference for patients in the lowest fasting glucose tertile ( p  = 0.044). These results support the biological plausibility of the association of interest. If confirmed in larger studies, our findings may help clarify the potentials of biomarkers related to energy metabolism in terms of prognosis definition, treatment assignment, and outcome interpretation for patients with high FIGO stage serous ovarian cancer. Abstract : Serous ovarian cystoadenocarcinoma with intense positive staining for glucose transporter protein 1 (GLUT1). A. GLUT1 x20; B. GLUT1x10.